All-optical Spectral Shuffling Applied to 16-QAM Signals - De Oliveira Santos, Melissa [UNESP] (2019)
All-optical spectral shuffling (AOSS) is a recently proposed physical layer encryption technique. In AOSS, multiple input signals are split in several spectral slices. These slices are then shuffled to form multiple encrypted signals. In fact, it is possible to transmit each shuffled signal by a different optical route. This strategy increases security because if an eavesdropper wants to detect information from a unique signal, he needs to tap at least one fiber per route. In this work, computer simulations are used to encrypt two 112 Gbps 16-quadrature amplitude modulation (QAM) signals and to propagate the shuffled signals by distinct optical routes. Our results reveal that the shuffled signals may be propagated by optical routes as long as 600 km. Besides that, we also investigate the situations i) where the signals travel by routes with different lengths and ii) where each route imposes different physical impairments to the encrypted signals.